Radiological study of Os trigonum and its clinical significance - Adibatti, Mallikarjun; Pitchandi, Muthiah; Bhuvaneswari, V (Asian Journal of Medical Sciences, 2021)
Background: Os trigonum (OST) is commonly located on the posterior aspect of the talus. It occurs as a result of secondary ossification center failing to fuse with the lateral tubercle of the posterior process of the talus; its incidence varies between 2 and 25%, and is more often bilateral. It occurs as an intra-articular Os, which is most often securely rooted to the lateral tubercle of the talus by a fibrocartilaginous synchondrosis. Aims and Objective: To determine the incidence, morphology, and distribution of Os Trigonum (OST). Materials and Methods: Retrospective 500 lateral foot radiographs view were studied to determine the incidence, morphology, and distribution of OST. Results: Incidence of OST in the present study was 6.6%, with predominantly round or ovoid in shape. OST was located on the posterolateral aspect of the talus. Conclusion: OST can be one of the causative factor responsible for Flexor hallucis longus tendonitis, OST syndrome, which occur in plantarflexion of the ankle, leading to compression of the OST between the distal tibia and the calcaneus. Hence, knowledge regarding the incidence, morphology, and distribution of OST is important for the radiologist, orthopedic surgeons to arrive at a correct diagnosis, which aids in the management of cases presenting with complaints of posterior ankle pain.